The diversity business: Narratives of international student recruitment in Canadian universities - Unruh, Natasha Marie; Lou, Nigel Mantou (Journal of International Students, 2026)
The ways universities frame international recruitment reflect core institutional values and influence efforts toward equity and inclusion. Previous research on racial diversity in the US suggests that institutions tend to rely on instrumental rationales (i.e., justify diversity in terms of institutional and economic benefits) over moral rationales (i.e., affirm diversity as an intrinsic value). We examined international recruitment narratives across 28 Canadian university websites and internationalization plans, yielding a total of 174 statements containing 338 rationales. We found that recruitment websites often featured diversity-related justifications, whereas internationalization plans primarily framed recruitment through broader economic and academic motivations. Across recruitment websites and internationalization plans, instrumental rationales significantly outweigh moral ones. Additionally, a negative correlation between instrumental and moral rationales suggests institutions tend to prioritize instrumental rationales over moral ones. Canadian universities frame international diversity in ways that align with institutional and majority-group interests, raising concerns about structural inequities for international students.